Oxidative stress as one of damage factors in early s experimental nephrolithiasis - Motin, Yu. G.; Zharicov, A. Yu.; Bryukhanov, V. M.; Zverev, Ya. F.; Lepilov, A. V.; Lampatov, V. V.; Motina, N. V. (Морфологія / Morphologia / Morfologìâ, 2011)
The results of kidney medulla morphological study from rats with ethylenglycol oxalate nephrolithiasis model are analyzed. Characteristics mitochondrial superoxide dismutase and malone dialdehyde expression during ethylenglycol oxalate nephrolithiasis modeling are evaluated. Registered morphological signs of oxidative damage activation and antioxidant enzyme attenuation in renal tissues.